BIG DATA IN THE ACCOUNTING PROFESSION: ADAPTATION, ISSUES, AND CHALLENGES - Sara Qistina Moggon@Jauhari; Rasyadah Abd Rashid; Vendwil Saimin; Mazurina Mohd Ali (International Journal of Accounting, Finance and Business, 2024)
This study investigated the utilization of Big Data in the accounting field, with a specific emphasis on the issues and challenges associated with improving the efficiency of forecasting models. The need for precise and dependable forecasting has grown significantly as organizations accumulate large quantities of data. Nevertheless, the integration of Big Data into accounting methodologies poses distinct and specific obstacles. This study investigated how accountants adapt to Big Data technology and discusses issues and challenges of Big Data in the forecasting models. It emphasizes the significance of accountants and experts in the accounting industry to be updated on emerging technologies to effectively utilize Big Data for enhanced forecasting in accounting.